2004
DOI: 10.1134/1.1738152
|View full text |Cite
|
Sign up to set email alerts
|

The light curve of supernova 1987A: The structure of the presupernova and radioactive nickel mixing

Abstract: Abstract-We have studied the influence of the presupernova structure and the degree of 56 Ni mixing on the bolometric light curve of SN 1987A in terms of radiation hydrodynamics in the one-group approximation by abandoning LTE and by taking into account nonthermal ionization and the contribution of spectral lines to its opacity. Our study shows that moderate 56 Ni mixing at velocities ≤2500 km scan explain the observed light curve if the density of the outer layers of the presupernova exceeds the value obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 39 publications
6
91
0
2
Order By: Relevance
“…The density is described by the exponential distribution ρ = ρ 0 exp(−v/v 0 ) with ρ 0 ∝ t −3 . The exponential law is fairly good for the bulk of the inner envelope where the power index |d ln ρ/d ln v| gradually increases outwards (e.g., Utrobin 2004). The parameters ρ 0 and v 0 are determined by M and E. We adopt as above M = 13 M ⊙ and E = 10 51 erg.…”
Section: Modeling Hα Asymmetrymentioning
confidence: 99%
“…The density is described by the exponential distribution ρ = ρ 0 exp(−v/v 0 ) with ρ 0 ∝ t −3 . The exponential law is fairly good for the bulk of the inner envelope where the power index |d ln ρ/d ln v| gradually increases outwards (e.g., Utrobin 2004). The parameters ρ 0 and v 0 are determined by M and E. We adopt as above M = 13 M ⊙ and E = 10 51 erg.…”
Section: Modeling Hα Asymmetrymentioning
confidence: 99%
“…Utrobin (2007) found that both this one-group approach and the multi-group approach of Baklanov et al (2005) measured similar ejecta mass and explosion energy for SN 1999em. The basic equations and details of the input physics, including calculations of mean opacities, are described in Utrobin (2004). The present version of the code includes additionally Compton cooling and heating.…”
Section: Model Overviewmentioning
confidence: 99%
“…The modeling of the SN explosion is performed using the spherically-symmetric hydrodynamic code with one-group radiation transfer (Utrobin 2004(Utrobin , 2007, which has been applied previously to other SNe IIP. Utrobin (2007) found that both this one-group approach and the multi-group approach of Baklanov et al (2005) measured similar ejecta mass and explosion energy for SN 1999em.…”
Section: Model Overviewmentioning
confidence: 99%
“…Fine structure in the Hα line (the "Bochum event") at 20-100 days after the explosion as well as redshifted emission lines at more than 150 days after explosion provides strong evidence for radial mixing of heavy elements into the upper envelope (Hanuschik & Dachs 1987;Phillips & Heathcote 1989;Spyromilio et al 1990). Updated models of the bolometric light curve at early epochs also require radial mixing of 56 Ni (Shigeyama & Nomoto 1990;Utrobin 2004). Direct Hubble Space Telescope (HST) imaging by Wang et al (2002) showed an elongated remnant ejecta, claimed to be bipolar and showing evidence for a jet-induced explosion.…”
Section: Introductionmentioning
confidence: 99%